From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome